청소년기 자녀를 둔 아버지 연구에 대한 동향분석 - 황지연; 김준미; 서은애; 신효정 (Human Ecology Research, 2023)
This research was conducted in order to examine previous studies on paternal parenting methods involving adolescent children in terms of their academic field, research period, method and subjects, and family variables. A total of 104 research publications from the period between 2003 and 2022 were investigated, with 99 quantitative research (43 theses and 56 academic journals) and five qualitative data sources. The analysis results show that the topic of fathers with adolescent children was the most studied in the field of education, and it rapidly increased from 2011 to 2014 and then rapidly decreased from 2019. The main subject of the studies was middle-school students, while most of the studies adopted a quantitative approach, with a minimal number of qualitative studies. Parenting studies were concentrated on father variables and several such studies were found to be related to positive resources such as self-esteem and self-efficacy as variables of adolescent children related to fathers’ parenting. The results of these studies provide meaningful implications for future research on the fathers of adolescent children and can be used as basic data for developing detailed education and programs.
Keywords: father; fathers with adolescent children; research trends